An Analysis of the Effectiveness of the Apexel Lens as a Non-Conventional Optical Device for Hilal Observation - Muhammad Khalil Mubarraq; Ravik Walhidayah; Ismail (Universitas Islam Negeri Mataram, 2026)
Crescent moon (Hilal) is a primary indicator to determine the onset of a new month in Hijri calendar, but access limitation to the conventional optical instrument such as telescope and theodolite remains a significant constaint across various strategic observation sites. This study aims to analyze the feasilibity of the Apexel telephoto lens as a non-conventional optical instrument for hilal observation, while also evaluating its potential as a screening tool to assessing the suitability of rukyat (crescent sighting) sites. The research employed a field-experimental approach, by comparing the optical performance of the Apexel lens mounted on a Google Pixel 5 with a standard astronomical telescope F70060 Telescope during Hilal observation conducted between November 21–24, 2025 at the Malikussaleh Observatory. The result demonstrate that Hilal image was successfully documented on November 23, 2025 with an altitude of 6° above the horizon. This outcome was significantly supported by favorable atmospheric conditions, characterized by cloud cover below 10%, which enabled the camera sensor to compensate for the Apexel lens's aperture limitations in capturing the low-contrast luminosity of the thin crescent. Conversely, detection attempts on other days failed due to adverse atmospheric conditions, wherein dense cloud cover attenuated hilal luminosity beyond the instrument's sensitivity threshold. From economic standpoint, this device represents a viable alternative for grassroots rukyat communities in remote areas, given its affordability and accessibility. Accordingly, Apexel telephoto lens has a potential to be a supplementary instrument for Hilal observation in the context of site exploration and public education, with the caveat that its performance is highly depends on sky clearance and astronomical parameters that meets the minimum visibility criteria.